Studi Hukum Pidana Atas Efektifitas Pelaksanaan Tilang Elektronik dalam Penanganan Pelanggaran Lalu Lintas (Studi Di Direktorat Lalu Lintas Polda Banten) - Mutie, Syeila; Asphianto, Aan; Mohas, Muhyi (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
Electronic tilang are not yet on target and are considered to be ineffective for all types of traffic violations and according to criminal law studies, electronic tickets are not effective because the sanction of imprisonment is not implemented. The method used in this research is normative juridical. Data collection techniques used in literature study research. The data analysis used in this research is descriptive analysis. The results of this discussion are that the function of criminal law in its function, both preventive (prevention) and repressive (control) for traffic violations using an electronic ticketing system during the period 2021, 2022 and 2023 shows an increase in the number of traffic violators and fewer confirmed ones because there are still Many people ignore etle and do not comply with the rules and are paid more than what is billed. The implementation of electronic ticketing in handling traffic violations by the Traffic Directorate of the Banten Regional Police has not been effective in dealing with traffic violations that occur on the highway because there is no National Police Regulation regarding the electronic ticketing mechanism and the fact shows that ETLE device cameras can only detect certain types of violations. on the highway and cannot cover the types of violations as regulated in Undang-Undang Nomor 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan. Apart from that, electronic tickets cannot be applied to motorized vehicles that use signs that do not provide a deterrent effect to drivers of motorized vehicles who commit traffic violations and cannot take action against all types of traffic violations because the CCTV camera depends on the electronic ticket and the specification of the violation depends on the digital ticket camera.